PENGARUH AKSES MODAL DARI LEMBAGA KEUANGAN DAN PRODUKTIVITAS LAHAN TERHADAP PENDAPATAN PETANI KELAPA SAWIT NAGARI OPHIR KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Wahyu Kurnia; Fajar Budiman; Yossi Eriawati; Hulfa Raihani; Feri Oki Nofendra (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2023)
This research uses a descriptive quantitative approach. The population in this study were oil palm farmers in Nagari Ophir. The number of salt farmers in Nagari Ophir is 120 palm oil farmers. Sampling was carried out using a random sampling method with a total of 92 oil palm farmers as respondents. The data results were processed using SPSS 16 tools to carry out research instrument tests, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests, determination tests (R2), t tests and f tests. The conclusion of this research is that based on the results of the hypothesis test carried out, it can be concluded that the variable access to capital has a positive and significant effect on the income of the people of Nagari Ophir, which is shown in the hypothesis t test with t-count (3,370) > t table (1,986) and sign value (0.01 < 0.05). Based on the results of the hypothesis test carried out, it can be concluded that the productivity variable has a significant positive effect on the income of the people of Nagari Ophir, which is shown in the hypothesis t test with a calculated t-value (3,484) > t-table (1,986) and a sign value (0.01 < 0.05). Based on the results of the hypothesis test carried out, it can be concluded that the variables Access to capital and productivity simultaneously (together) influence the income of the people of Nagari Ophir which can be seen from the results of the F test with the value of F-count (14.140) > F-table (2.71) and sign value (0.000 < 0.05).